2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944455
|View full text |Cite
|
Sign up to set email alerts
|

Towards continuous monitoring of pulse rate in neonatal intensive care unit with a webcam

Abstract: We describe a novel method to monitor pulse rate (PR) on a continuous basis of patients in a neonatal intensive care unit (NICU) using videos taken from a high definition (HD) webcam. We describe algorithms that determine PR from videoplethysmographic (VPG) signals extracted from multiple regions of interest (ROI) simultaneously available within the field of view of the camera where cardiac signal is registered. We detect motion from video images and compensate for motion artifacts from each ROI. Preliminary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 23 publications
0
58
0
Order By: Relevance
“…The essential difference between these rPPG methods is in the way of combining RGB-signals into a pulse-signal. A better understanding of the core rPPG methods could benefit many systems/applications for video health monitoring, such as the monitoring of heart-rate [7]- [11], respiration [8], SpO 2 [8], [12], blood pressure [13], neonates [14], [15], and the detection of atrial fibrillation [16] and mental stress [17].…”
Section: Introductionmentioning
confidence: 99%
“…The essential difference between these rPPG methods is in the way of combining RGB-signals into a pulse-signal. A better understanding of the core rPPG methods could benefit many systems/applications for video health monitoring, such as the monitoring of heart-rate [7]- [11], respiration [8], SpO 2 [8], [12], blood pressure [13], neonates [14], [15], and the detection of atrial fibrillation [16] and mental stress [17].…”
Section: Introductionmentioning
confidence: 99%
“…Another work [6] reports on the use of distant pulse rate measurement in neonates. The system was based on a high definition (HD) webcam, while the final image resolution was only 640 × 480.…”
Section: Related Workmentioning
confidence: 99%
“…Recent trends [3][4][5][6][7] in validating camera-based pulse rate monitoring methods in neonatal clinical settings are highlighted in Table 1. The first medical study of camera-based pulse rate monitoring for neonates was reported by Scalise et al [4].…”
Section: Current Trendsmentioning
confidence: 99%
“…They explored different scenes with challenging conditions for 19 infants in durations of 1 to 5 mins. Klaessens et al [5], Mestha et al [6] and Villarroel et al [7] all report clinical studies of 7, 8 and 2 (2 are reported out of an ongoing study of 40) infants respectively. However, the details of the scenes recorded with challenging conditions are not reported or are removed from the analysis.…”
Section: Current Trendsmentioning
confidence: 99%